Canary in the Mine and the Concerns of Research Councils, Applied Ethnomusicologists, and Museum Professionals - Sparling, Heather (Material Culture Review, 2016)
In this paper, I share the story of an interactive, digital exhibit called Canary in the Mine: Nova Scotia Mining Disasters and Song both to inspire future music-centred exhibits and to offer insights into the experience of a non-museum professional developing an exhibit. I concentrate on the ways in which this exhibit exemplifies a response to pressing concerns of three distinct but similarly invested groups. First, the exhibit is an example of knowledge mobilization, a key concern for research councils and funding agencies that can be approached to fund projects such as Canary in the Mine. Second, the exhibit is an example of applied ethnomusicology, an area of growing interest and activity for many ethnomusicologists who seek to solve concrete problems with music and music knowledge. Finally, the exhibit offers museum professionals a model for using digital technologies to incorporate intangible culture into their institutions, a topic of increasingly pressing significance since UNESCO enacted its Convention for Safeguarding Intangible Cultural Heritage in 2003.